Stimulus promosi penjualan, marketplace display, dan motivasi belanja hedonis terhadap impulse buying di kalangan wanita milenial - Isalman; Ilyas; Farhan Ramadhani; Nurul Ittaqullah (Jurnal Ilmu Manajemen, 2024)
This research aims to determine the effect of sales promotions on hedonic shopping motivation and impulse buying. To determine the influence of marketplace displays on hedonic shopping motivation and impulse buying. To determine the influence of hedonic shopping motivation on impulse buying. The type of research used is explanatory research. This research focuses on the group of millennial women who actively shop online in the marketplace. Data collection was carried out from July to September 2023. The number of samples was 200 respondents. Data analysis uses Structural Equation Modeling (SEM) with smartPLS 3.0. The results of the analysis show that sales promotions have an effect on impulse buying, but do not have a significant effect on hedonic shopping motivation. Marketplace displays influence hedonic shopping motivation, but do not significantly influence impulse buying. Hedonic shopping motivation influences impulse buying. In addition, hedonic shopping motivation mediates the relationship between marketplace displays and impulse buying, but does not mediate the influence of sales promotions on impulse buying. These findings provide information for marketplace sellers in using various sales promotions to accelerate impulse buying decisions among millennial women, as well as making efforts to organize marketplace displays that can foster hedonic shopping motivation and trigger impulse buying among millennial women.